2017
DOI: 10.1016/j.actamat.2016.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of ultrathin sputter deposited porous amorphous Al2O3 films

Abstract: The determination of the mechanical properties of porous amorphous Al 2 O 3 thin films is essential to address reliability issues in wear-resistant, optical and electronic coating applications. Testing the mechanical properties of Al 2 O 3 films thinner than 200 nm is challenging, and the link between the mechanical behavior and the microstructure of such films is largely unknown. Herein, we report on the elastic and viscoplastic mechanical properties of amorphous Al 2 O 3 thin films synthesized by reactive ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 46 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Experimental observations for Al2O3 at the nanoscale have been mixed: some measurements show prerequisites for plastic deformation at room temperature (15)(16)(17)(18), while others display fully brittle behavior (19)(20)(21).…”
mentioning
confidence: 99%
“…Experimental observations for Al2O3 at the nanoscale have been mixed: some measurements show prerequisites for plastic deformation at room temperature (15)(16)(17)(18), while others display fully brittle behavior (19)(20)(21).…”
mentioning
confidence: 99%
“…In particular, different sputtering pressures were used in the two sets of experiments. It has been previously reported that the sputtering pressure impacts the density, stiffness and strength of sputtered films (van der Rest et al, 2017;Kumari et al, 2018). It is therefore possible that it also affects the rate sensitivity, since rate sensitivity and strength are intrinsically coupled through the micro-mechanisms of plastic deformations in amorphous materials.…”
Section: Comparison To Experimental Resultsmentioning
confidence: 96%
“…The average hardness of both as-grown samples deposited by the two techniques is in agreement with the values reported in the literature for amorphous coatings, i.e., in the range from 5 to 12 GPa. [17,40,41,43,[45][46][47][48] Higher hardness values, in the range 8-20 GPa, are then usually found on transition alumina coatings. [17,18,40,41] Accordingly, both high temperature annealed coatings showed a higher hardness with respect to the corresponding unannealed films, as expected due to the transition from a totally amorphous alumina film to a crystalline structure containing the harder transition phases.…”
Section: Resultsmentioning
confidence: 99%